Challenging puzzles - Vout, Colin; Gray, Gordon (Cambridge : New York : Cambridge University Press, 1993)
Designed for all recreational mathematicians from the age of 14 upwards. There are 100 puzzles in all, graded according to difficulty, with hints and solutions to most and suggestions for open ended topics where exact solutions are impossible
Keywords: Mathematical recreations; Puzzles